DATA PROCESSING CENTER FOR RADIOASTRON PROJECT HARDWARE OPTIMIZATION - Shatskaya, M.; Abramov, A.; Guirin, I.; Isaev, E.; Kostenko, V.; Likhachev, S.; Primakov, A.; Seliverstov, S.; Fedorov, N. (Одеські астрономічні публікації, 2013)
The RadioAstron is an international space VLBI project led by the Astro Space Center of Lebedev Physical Institute inMoscow,Russia. The payload - Space Radio Telescope, is based on spacecraft Spektr-R, that have been designed by the Lavochkin Association. The Spektr-R space craft was successfully launched 18 th July 2011. In this article we want to summarize Radioastron data processing center work during 2 last years. Tasks facing of the scientific data processing center are organization of service information exchange, collection of scientific observations, storage of scientific observations, processing of scientific observation data Radioastron project.